Analysis of the Influence of Company Culture, Work Environment and Compensation on Employee Performance of PT Hasjrat Abadi Ambon - Leatemia, Adriana; Pentury, GM; Risambessy, A. (SEAN Institute, 2024)
The existence of human resources in a company plays a very important role, therefore human resource management must be carried out professionally in order to create a balance between employee needs and demands and abilities. Corporate culture is a philosophy that a company must adhere to in a company because it has values, rules and norms that must be adhered to by all employees, both leaders and subordinates. The work environment is a measuring tool that will influence employee performance if the work environment in an agency is good. Compensation within the company must be managed well. So that it can be accepted by both parties in the hope of improving employee performance. This research aims to analyze and explain the influence of company culture, work environment and compensation on employee performance, at PT. Eternal Desire. Research object at PT. Hasjrat Abadi Using a saturated sampling technique, the sample size was 35 employees. The data analysis method uses Multiple Linear Regression using the SPSS vs 23 software program. The research results prove that there is a positive influence between company culture and its significant influence on employee performance. Compensation has a significant influence on employee performance. The work environment has a significant effect on employee performance, a variable that has been researched currently by adding other variables such as organizational climate by expanding the research location.